2015
DOI: 10.1016/j.bbamem.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels in the regulation of apoptosis

Abstract: Apoptosis, a type of genetically controlled cell death, is a fundamental cellular mechanism utilized by multicellular organisms for disposal of cells that are no longer needed or potentially detrimental. Given the crucial role of apoptosis in physiology, deregulation of apoptotic machinery is associated with various diseases as well as abnormalities in development. Acquired resistance to apoptosis represents the common feature of most and perhaps all types of cancer. Therefore, repairing and reactivating apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(138 citation statements)
references
References 263 publications
3
119
0
3
Order By: Relevance
“…These channels allow the cell to shrink (apoptotic volume decrease, AVD) by releasing anions and organic osmolytes to the extracellular space, which resembles the osmotic driving force for water exit ( Fig. 1) (Kondratskyi et al 2015;Lang et al 2007;Lang and Hoffmann 2012). Initial AVD in apoptosis is essential; its suppression strongly attenuates apoptosis and also reflects a mechanism for cancer cells to escape from apoptotic cell death (Maeno et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…These channels allow the cell to shrink (apoptotic volume decrease, AVD) by releasing anions and organic osmolytes to the extracellular space, which resembles the osmotic driving force for water exit ( Fig. 1) (Kondratskyi et al 2015;Lang et al 2007;Lang and Hoffmann 2012). Initial AVD in apoptosis is essential; its suppression strongly attenuates apoptosis and also reflects a mechanism for cancer cells to escape from apoptotic cell death (Maeno et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…In terms of time-course, apoptotic volume decrease (AVD) occurs in two phases, an initial phase that starts 0.5-2 hours after exposure to the inductor and a late phase detected about 3 hours later. The two phases of AVD are accomplished by the same mechanism that includes outward fluxes of K 1 and Cl -moving across specific channels and a decrease in osmolyte intracellular concentration and water outflow resulting in AVD (Kondratskyi et al, 2015). It has yet to be determined whether this decrease in cell volume is a passive factor or an active signal in the induction of apoptosis, but evidence does exist that points to an explicit role for volume decrease in the apoptotic process; blockade of the main osmolyte pathways that reduce AVD impairs the progression of apoptosis (Yu and Choi, 2000;Grishin et al, 2005).…”
Section: Channels Involved In Volume Changes In Necrotic and Apoptotimentioning
confidence: 99%
“…15 In vivo studies have suggested that diltiazem, an L-type calcium channel blocker (CCB), may reduce the concentration of calcium precipitates at the basolateral membrane of the OHCs. 16 There is also evidence demonstrating that L-type calcium channels can be localized to the inner ear and play a role in the pathogenesis of acoustic injury.…”
mentioning
confidence: 99%